AN APPROXIMATION TO DETERMINE CORROSION AND MECHANICAL BEHAVIOR OF TI-BASED ALLOYS - Yilmaz, Yesim; Demiroren, Hulya (World Scientific Publ Co Pte Ltd, 2021)
Titanium and its alloys used in biomaterial applications are preferrably the cause of high-corrosion resistance properties in addition to having good mechanical properties. Commercially pure Ti (CPTi) (Grade 2), Ti6Al4V (Grade 5) and Ti6Al4V-ELI (Grade 23) samples are used as biomaterials exposed to 750 degrees C and 1060 degrees C for 1 h. The samples were cooled in air after heat treatment at 750 degrees C, the other samples were cooled in water after heat treatment at 1060 degrees C. The free-heat treatment samples are as producted. Microstructures of heat-treated samples and non-made samples by comparison were evaluated before and after corrosion process microstructures and tensile strengths. Test solution is 0.5 mol H2SO4 + 1 mol HCl mixture. The corrosion resistance of the titanium samples was evaluated. Microstructure images were monitorized on optical and SEM microscopes. In this paper, the effect of heat treatment was determined on the microstructure, mechanical properties and corrosion resistances of the material. As a result, heat treatment is useful on corrosion resistance of alloyed samples.
Keywords: Biomaterials; titanium; corrosion; heat treatment; mechanical behavior